New Technique for the Treatment of Anterior Hypospadias Doubles-Y Glanuloplasty prospective Evaluation and A Systematic Review - M Lahfaoui; H Benhaddou (Archive of Urological Research - Peertechz Publications, 2020)
Introduction: Hypospadias is the ectopic closure of the urethral meatus at the ventral surface of the penis. The diversity of techniques proposed to treat hypospadias has caused a great debate among urologists about the effectiveness of these techniques. The objective of our study is to develop the double Y glanduloplasty technique, expose and compare the results of this technique to improve the management of anterior hypospadias. Material and method: Our prospective study is conducted on 18 patients treated for anterior hypospadias with the double Y glanduloplasty technique between January 1, 2017 and June 30, 2019 in the pediatric visceral and urogenital surgery department at Mohamed VI- Oujda University Hospital. Results and discussion: Previous hypospadias was generally discovered by the mother in 45%. The average age of the PEC was 4.32 years. The anatomical varieties operated by the DYG technique were balanic and balanopruputial with equal percentages, 50% each. The most common malformation was incomplete foreskin (45%), followed by penis curvature (33%) and cryptorchidism (16%). 78% of the cases operated on were uncircumcised. The after-effects of the operation: were simple. The complication rate was 16% (2 cases of fistula, 1 case of partial meatus stenosis). 83% of parents were satisfied with the results. Conclusion: Comparison of double Y glanduloplasty with other techniques used in anterior hypospadias shows that complications are much less frequent with DYG, with satisfactory aesthetic and functional results. So we strongly recommend the use of this technique in glandular hypospadias with a mobile meatus and without deep curvature of the penis.